Helena Ostrowicka, (2022). Problematyzacje. Studia nad dyskursem w badaniach edukacyjnych. Kraków: Oficyna Wydawnicza Impuls, ss. 232 - Kopińska, Violetta (Studia Edukacyjne, 2024)
Recenzja: Helena Ostrowicka, (2022). Problematyzacje. Studia nad dyskursem w badaniach edukacyjnych. Kraków: Oficyna Wydawnicza Impuls, ss. 232